Political ideology and justification of the inequity in two samples of the city of Lima from opposing socioeconomic sectors - Molina Guzmán, Juvenal (2015)
This research analyzes and compares the association between political ideology and justification of inequity in two samples from Lima, city, which are in different socio-economic situations: (a) a group with a very favorable economic situation and higher educative levels or postgraduate, which was called socially advantaged group; and (b) a group in situation of poverty with technical studies as maximum, named socially disadvantaged group. The results show that the socially disadvantaged group presents higher scores in Right-Wing Authoritarianism (RWA) and some of the dimensions of the justification of inequity. Furthermore, another important finding is that the socially disadvantaged group appears to show adifferent ideological organization in comparison with the socially advantaged group, which shows an ideological organization more consistent with the found in previous studies in urban areas.